2006
DOI: 10.1021/jf052811y
|View full text |Cite
|
Sign up to set email alerts
|

Redox Instability Induced by 4-Hydroxy-2-nonenal in Porcine and Bovine Myoglobins at pH 5.6 and 4 °C

Abstract: Myoglobin (Mb) redox stability affects meat color and is compromised by lipid oxidation products such as 4-hydroxy-2-nonenal (HNE). Pork lipids are generally more unsaturated and would be expected to oxidize readily and produce more oxidation products than beef. Supranutritional supplementation of vitamin E improves Mb redox stability of beef but not pork. The present study investigated HNE-induced redox instability in porcine and bovine myoglobins at 4 degrees C and pH 5.6. Oxymyoglobin (OxyMb) was incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 39 publications
2
50
3
Order By: Relevance
“…HNE is an α, β-unsaturated aldehyde, generated by the oxidation of ω-6 polyunsaturated fatty acids in the biological membranes (Schneider, Tallman, Porter, & Brash, 2001). The prooxidative effect of HNE has been reported in different Mb species, such as tuna (Lee, Joo, Alderton, Hill, & Faustman, 2003), pork (Lee, Phillips, Liebler, & Faustman, 2003;Suman, Faustman, Stamer, & Liebler, 2006, horse (Faustman, Liebler, McClure, & Sun, 1999) and beef (Alderton, Faustman, Liebler, & Hill, 2003;Suman et al, 2007). Molecular basis of lipid oxidation-induced Mb oxidation has been investigated extensively using MS and proteomic tools.…”
Section: Lipid Oxidation-induced Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…HNE is an α, β-unsaturated aldehyde, generated by the oxidation of ω-6 polyunsaturated fatty acids in the biological membranes (Schneider, Tallman, Porter, & Brash, 2001). The prooxidative effect of HNE has been reported in different Mb species, such as tuna (Lee, Joo, Alderton, Hill, & Faustman, 2003), pork (Lee, Phillips, Liebler, & Faustman, 2003;Suman, Faustman, Stamer, & Liebler, 2006, horse (Faustman, Liebler, McClure, & Sun, 1999) and beef (Alderton, Faustman, Liebler, & Hill, 2003;Suman et al, 2007). Molecular basis of lipid oxidation-induced Mb oxidation has been investigated extensively using MS and proteomic tools.…”
Section: Lipid Oxidation-induced Oxidationmentioning
confidence: 99%
“…Molecular basis of lipid oxidation-induced Mb oxidation has been investigated extensively using MS and proteomic tools. Covalent modification of amino acids via aldehyde adduction was concluded as the reason for lipid oxidation-induced Mb oxidation (Faustman et al, 1999;Alderton et al, 2003;Lee, Phillips, et al, 2003;Suman et al, 2006Suman et al, , 2007. Cysteine, lysine, arginine and histidine are the most susceptible amino acids for nucleophilic attack by HNE for Michael addition (Bolgar & Gaskell, 1996;Isom et al, 2004;Uchida & Stadtman, 1992).…”
Section: Lipid Oxidation-induced Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…can be attributed to the protective effect of pH on oxymyoglobin and lipid oxidation. In-vitro experiments utilizing purified myoglobin also demonstrated greater stability of oxymyoglobin at pH 7.4 than at pH 5.6 (Suman et al, 2006). Previous research also reported lower TBARS values in dark-cutting beef than normal-pH steaks (Sawyer et al, 2009).…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, differences in the amino acid sequence influence the interaction between myoglobin and lipid oxidation products. Beef myoglobin was more susceptible to lipid oxidation-induced oxidation than was pork myoglobin (Suman, Faustman, Stamer, & Liebler, 2006). Further investigations (Suman, Faustman, Stamer, & Liebler, 2007) suggested preferential adduction of aldehydes at the proximal histidine residue (position 93) in beef myoglobin as a reason for the increased propensity of beef myoglobin to undergo lipid oxidation-induced oxidation.…”
Section: Nomentioning
confidence: 96%